A CONSTRUCTIVIST METHOD FOR THE ANALYSIS OF NETWORKED COGNITIVE COMMUNICATION AND THE ASSESSMENT OF COLLABORATIVE LEARNING AND KNOWLEDGE-BUILDING - Campos, Milton (Online Learning, 2004)
This article presents a discourse analysis method designed to study networked cognitive communication processes in knowledge communities, such as conceptual change, higher order learning and knowledge building. The method is grounded on genetic epistemology and integrates constructivist and socioconstructivist theoretical concepts. The sentence (understood as judgment) is chosen as the unit of analysis, and the application of the method is further explained. In addition, a study of transcripts in an asynchronous networked community of nurses illustrates the method and demonstrates how conceptual change, collaborative learning and knowledge building can be identified. Advantages and limitations of the method are also discussed.